2004
DOI: 10.2298/mpns0404125z
|View full text |Cite
|
Sign up to set email alerts
|

The role of laparoscopy in gynecologic oncology

Abstract: In some patients and when performed by a skillful surgeon, gynecologic oncologist familiar with advanced laparoscopic techniques, laparoscopy results with less surgical trauma, reduced blood loss and hospitalization, and faster recovery. The complication rate has been found to increase as the complexity of the operation rises, but it is not higher than in open surgery. Preliminary studies show that recurrence and survival rates are comparable to those reported for patients treated by a standard abdominal appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Several studies in the past have also demonstrated a significant discrepancy between the CT and the surgical findings on bowel involvement ( 16 , 30 , 31 ). In the past decades, a few groups have introduced an exploratory laparoscopy (EXL) before laparotomy ( 32 35 ). The advantages of EXL are multiple, including a correct diagnosis based on the histology of tissue biopsy, precise evaluation of disease spread, and better selection of the patients for ultra-radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the past have also demonstrated a significant discrepancy between the CT and the surgical findings on bowel involvement ( 16 , 30 , 31 ). In the past decades, a few groups have introduced an exploratory laparoscopy (EXL) before laparotomy ( 32 35 ). The advantages of EXL are multiple, including a correct diagnosis based on the histology of tissue biopsy, precise evaluation of disease spread, and better selection of the patients for ultra-radical surgery.…”
Section: Discussionmentioning
confidence: 99%